Penguatan Profil Pelajar Pancasila bagi Murid MTs. Baitis Salmah Ciputat dalam Menciptakan Generasi Sumber Daya Manusia yang Unggul - Syarifah Ida Farida; Rahadyan Tajuddien; Cornelia Dumarya Manik (Indonesian Journal of Society Engagement, 2022)
This community service activity aims to provide training and counseling to produce a generation of superior human resources. the method used in this activity is in the form of training and motivational encouragement delivered in the form of lectures and audiences conducted face-to-face. The objects in this activity are the students of MTs. Baitis Salmah Ciputat, and this activity is carried out in the Multipurpose Room of MTs. Baitis Salmah Ciputat which is located at Jl. Baitis Salmah Ciputat Mosque, Sawah Baru Village, Ciputat District, South Tangerang. The results showed that after the implementation of this activity, the students showed an increased enthusiasm to continue learning both at home and outside the classroom and understood how important it is to have superior human resources who are able to compete nationally and globally, and to be a human being who benefits his fellow man, his family, religion and nation and state. Students understand the character in the Pancasila Student Profile and can practice in accordance with Pancasila Values.